2007
DOI: 10.1152/jn.00460.2007
|View full text |Cite
|
Sign up to set email alerts
|

Frontoparietal Activation With Preparation for Antisaccades

Abstract: Several current models hold that frontoparietal areas exert cognitive control by biasing task-relevant processing in other brain areas. Previous event-related functional magnetic resonance imaging (fMRI) studies have compared prosaccades and antisaccades, which require subjects to look toward or away from a flashed peripheral stimulus, respectively. These studies found greater activation for antisaccades in frontal and parietal regions at the ends of long (>or=6 s) preparatory periods preceding peripheral stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
120
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(146 citation statements)
references
References 66 publications
23
120
3
Order By: Relevance
“…Greater pre-stimulus activation in the frontal cortex on correct when compared with error trials has also been reported by an event-related potential study [25]. Recently, an electroencephalogram study reported a decrease in ongoing beta-power (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) in frontal cortex on error trials during the preparatory period on antisaccade trials [26]. In general, data from human imaging studies indicate that increased PFC activation, particularly of the region of the middle frontal gyrus, is associated with correct performance on the antisaccade task.…”
Section: Evidence From Functional Imagingmentioning
confidence: 58%
“…Greater pre-stimulus activation in the frontal cortex on correct when compared with error trials has also been reported by an event-related potential study [25]. Recently, an electroencephalogram study reported a decrease in ongoing beta-power (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) in frontal cortex on error trials during the preparatory period on antisaccade trials [26]. In general, data from human imaging studies indicate that increased PFC activation, particularly of the region of the middle frontal gyrus, is associated with correct performance on the antisaccade task.…”
Section: Evidence From Functional Imagingmentioning
confidence: 58%
“…1 B). They were clustered at the coordinate (30,2,57) in the standard brain of the Montreal Neurological Institute (MNI), which corresponds to the FEF (Ford et al, 2005;Grosbras et al, 2005;Brown et al, 2007). In the control experiment, the procedure was as above with the exception that we delivered TMS to the postcentral gyrus (mean coordinate: 28, Ϫ42, 66), following the procedure of a previous TMS-EEG study (Taylor et al, 2007b).…”
Section: Methodsmentioning
confidence: 99%
“…This includes neurons that are active during fixation and neurons that seem to prepare for a saccade. As revealed with fMRI, preparation for an antisaccade activates DLPFC more strongly than any other brain region (Brown et al 2007). Neuropsychological evidence also suggests that this area plays an important role in the control of voluntary eye movements.…”
Section: Dlpfcmentioning
confidence: 95%